The contribution and impact of management control on the performance of public hospitals in Morocco: moving beyond the "New Public Management" - CHERKAOUI DEKKAKI , Achraf; ELHAMMA , Azzouz (Revue Internationale du Chercheur, 2024)
The various crises over the past decades have prompted the State to rationalize its budget management and establish governance instruments to instill a sense of responsibility among organizations and their stakeholders, often associated with the movement called "New Public Management" (NPM). In Morocco, the public sector reform through NPM has impacted all areas, especially healthcare. However, hospital structures have yet to experience significant evolution to meet the population's changing needs in terms of care provided despite constraints related to human, financial, and logistical resources. This situation raises questions about the actual benefits of NPM (and its implementation) in organizing the public hospital sector. This article proposes a framework for analyzing the principles and tools of NPM, with particular emphasis on "Management Control," to expose its development in the public sector, specifically within public hospitals. It also examines the role of management control in improving hospital performance in the face of various inquiries regarding the contributions made by NPM to the Moroccan public sector.